Reliability and Validity of the Portable Analyses of Temporal and Spatial Gait Parameters in Patients with Stroke - Wentong ZHANG; Jinyuan NIU; Guangxu XU; Dianhuai MENG; Naixian SHI; Jiawei RUAN (康复学报)
Objective:To explore the reliability and validity of the portable analyses of the temporal and spatial gait parameters in patients with stroke.Methods:Forty patients with stroke were recruited for this study. All patients received three times of gait analysis Pearson by the portable analyses on the same day. The first gait analysis was tested by the operator, the second and the third were tested by another operator. We also recorded the temporal and spatial gait parameters by using the footprint method in the thrice gait analysis. The t test, interclass correlation coefficient (ICC) and Pearson correlation coefficient were used to evaluate the reliability and validity of the portable analyses.Results:There was no significant difference of the temporal and spatial gait parameters (cadence, walking speed and step length) between the first portable analyses and the seconded portable analyses (P>0.05). Test-retest comparisons with the Gait Watch apparatus generated ICCs for the temporal and spatial parameters ranging between 0.90-1.0 indicating good test-retest reliability. There was high correlation between the portable analyses and the footprint method methods.Conclusion:Measurements of cadence, stridelength, walking speed and step length with the portable analyses have a high reliability and validity and either can be used in clinical walking assessment.